Manajemen Diet dan Kualitas Hidup Pasien Penyakit Ginjal Kronik Yang Menjalani Hemodialisis di Rumah Sakit - Asyrofi, Ahmad; Arisdiani, Triana (Journal of Holistic Nursing Science, 2020)
Patients with chronic kidney disease (CKD) undergoing hemodialysis (HD) experience a decrease in physical health status that affects their quality of life. CKD patients need proper self-care management, including diet management to manage and maintain their health status. The purpose of this paper is to analyze the differences in the quality of life of CKD patients undergoing hemodialysis between the various dietary management they undertake. Method: cross-sectional study design, samples of all CKD patients undergoing hemodialysis were 60 respondents. Dietary management measures are the subscale Hemodialysis Patient's Self-care Management Scale (HPSMS): dietary regulatory; food safety; and therapeutic diet implementation. Quality of life using the Kidney Disease Quality of Life (KDQOL) SF 1.3 instrument. The univariate analysis uses the central tendency and proportion, and bivariate analysis uses the Fisher-exact test. Results: the average age of 47.3 years, 53.3% of men, the median value of HD 10.5 months long, 58.3% did not work. 83.3% poor diet management, safe 83.3% poor food, 68.3% poor therapeutic diet implementation, and 81.7% poor quality of life of CKD patients. There was a significant difference in the quality of life of CKD patients between various dietary arrangements, (p=0.0001), safe food (p=0.013), and implementation of a therapeutic diet (p=0.027). Conclusion: A good diet management has the opportunity to improve the quality of life of CKD patients.